Elaboration of food products with biofortified sweet potatoes: Characterization and sensory acceptability - Santos, Felipe Nardo dos; Duarte, Lucas Nachtigal; Samborski, Tarcísio; Mello, Alexandre Furtado Silveira; Kringel, Dianini Hüttner; Severo, Joseana (SciELO, 2021)
Beauregard sweet potato is an orange color crop rich in β-carotene, a precursor of vitamin A. β-carotene improve immunity and decrease of incidence of degenerative diseases. The objective of this work was to introduce sweet potato in the diet through of some food products, such as bread, cake and sweets. The effect of processing on the chemical composition, as well as the quantification of phenols and total carotenoids, antioxidant activity, and sensory acceptability were evaluated. Cakes and coconut sweets presented higher levels of carotenoids. Higher phenolic and antioxidant activity were verified in cocoa sweets. All foods had good acceptability: 86% for bread, 83.3% for cake and 84,4%, and 86% for coconut and cocoa sweets, respectively. Servings of 95g of roasted sweet potato, 330g of bread, 182g of cake, 187g of coconut sweet and 391g end of cocoa sweet, would provide the recommended daily intake of vitamin A for children 10 years and older. It was concluded that the elaboration of foods containing sweet potato is a viable alternative to inserting biofortified foods into the human diet.